PERAN PENDIDIKAN DALAM BIMBINGAN KONSELING UNTUK MENINGKATKAN MOTIVASI BELAJAR ANAK - Wulandari, Herlina (Departemen Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2023)
Learning is a form of assistance provided by the teacher so that the process of obtaining knowledge and knowledge can occur, mastering skills and character, forming attitudes and beliefs in students. in the educational environment problems for students who experience delays in the power of thinking, delays in writing, and reading. The teacher in this teaching and learning process becomes a facilitator for students who have difficulty reading and writing. In the guidance and counseling process, if there are children who have difficulty reading and writing, the teacher can identify the problems and needs of students, besides that the teacher diagnoses what causes the child to experience delays in reading and writing.Learning difficulties can also occur in children who under standard abilities, does not only occur in students with low abilities. Learning difficulties can also befall students and students who have normal or average academic standards. The steps for solving student learning difficulties in counseling guidance, namely talking to the principal in advance about having students with problems. Then look for ways that need to be done to deal with these problems, it can be concluded that the role of the homeroom teacher acts as a guide so that students can achieve educational goals that are directed to be good in the entire educational process, the guidance counselor collaborates with the subject teacher or homeroom teacher with work The same between the three can make it easier for students to increase learning motivation. The homeroom teacher also acts as a guide who always directs the behavior of students, by showing students things that are not done correctly and asking them to do it again correctly and as well as possibleKeyword: learning motivation, counseling guidance